Peran Pembiayaan Syariah Terhadap Pengembangan UMKM: Studi Pada Pengusaha Emping Melinjo di Kabupaten Pandeglang - Isti Nuzulul Atiah; Najmudin Najmudin; Moh. Ainun Najib (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2020)
The Role of Sharia Financing for the Development of MSMEs: A Study of Emping Melinjo Enterpreneurs in Pandeglang District. Islamic finance is one of the programs owned by Islamic banking to play and develop its financial assets, especially to finance the real sector such as MSMEs. The types of Islamic finance itself are diverse, ranging from mudaraba, musharaka and so on. However, an understanding of the types of Islamic financing and their uptake still tends to ocuur in urban areas that are still lagging behind, such as Pandeglang Regency are still inadequate, while the SME sector emping gums a lot and mushroomed in the area. This research uses descriptive qualitative method with Miles and Huberman data analysis models. This research is oriented to find out the type of Islamic financing that is of interest by emping melinjo enterpreneurs in Pandeglang Regency, factors that influence the choice of financing and capital management of Islamic financing by emping melinjo enterpreneurs in Pandeglang Regency. The results of this study are the types of financing provided to emping melinjo enterpreneurs in Pandeglang district, namely murabahah and qardhul hasan, factors influencing the selection of these financing are because both of the financing are considered easier and simpler, besides qardhul hasan financing is more profitable because the entrepreneur doesn’t need add margin to the lender for the principal funds lent.